Progress in Demand Response and It’s Industrial Applications - Siddiquee, S. M. Shahnewaz; Howard, Bianca; Bruton, Ken; Brem, Alexander; O'Sullivan, Dominic T. J. (Frontiers in Energy Research, 2021)
Achieving energy flexibility is becoming a key concern for energy system planners that manage intermittent and variable generations. Industries have enormous potential to deliver large-scale energy flexibility through demand response (DR) programs. This industrial demand flexibility achieved through the demand response programs will enable widespread adoption of renewable sources in the electricity grid network. This paper aims to provide a comprehensive review of on-demand response and it's industrial application by addressing: 1) Current research status, 2) Current stages of demand response applications in industries, and 3) Barriers in the deployment of DR. This study shows that there is significant research progress in recent years in the field of DR. It also shows potential applications of DR programs in industries. However, the study found several technical, policy, and financial barriers still exist, limiting the widespread adoption of DR. Thus, this paper offers recommendations on technical, policy, and financial measures needed to over-come the barriers and help facilitate the utilization of demand response potential, especially in industries.